MAKING IT SERVICE PORTFOLIO DOCUMENTS AT PT BANK MANDIRI TASPEN KEDIRI BRANCH USING ITIL FRAMEWORK VERSION 3, 2011 EDITION - Rendy Fadly, Mochammad; Sutomo, Erwin; Mirza Maulana, Yoppy (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2019)
Identification value chain makes it easy to know business processes have been supported by IT services or not supported by IT services. PT Bank Mandiri Taspen subdivision Kediri not all business processes are supported by IT services. This has an impact on decision making to analyze and invest IT services. The technology capabilities cannot work optimally and operational activities cannot excedd the specified goal limits. The result a catalog IT service be required making IT service portfolio documents using Information Technology and Infrastructure Library (ITIL). The preparation stage using service strategy namely define, analyze, approve and charter. Methods to support the preparation of IT service portfolio documents include value chain, balanced scorecard, cost model, return on investment, ranti’s IS/IT generic business value and communication matrix. The results of identification will produce a catalog IT service use service charter in its delivery. The final stage conclusions and suggestions.